Analysis of Breakfast Habits on The Incidence of Anemia - Andiarna, Funsu (International Conference on Sustainable Health Promotion, 2018)
Anemia is a situation where the level of hemoglobin in the blood is less than normal. Anemia is a common nutritional problem in the world, especially in developing countries than developed countries. The prevalence of anemia is estimated to be 9% in developed countries, while in developing countries prevalence 43%. High-risk adolescents suffer from anemia. Increasing activities, social life, as well as a flurry of adolescents will affect their eating habits. Food consumption patterns are often irregular, often snacks, often not having breakfast, and not having lunch at all. The purpose of this research is to know the existence of a correlation between teens who have a habit of breakfast with the incidence of anemia. This study is an analytic observational study with a cohort approach. Data collection techniques with accidental sampling technique. Characteristics of respondents based on age, which is late adolescence 15-23 years. The measuring instrument used to measure anemia status (Hb level) using the Hb Sahli method, while to measure breakfast habits using a questionnaire measuring instrument. The measurement results using Fisher’s Exact test obtained that the value of ρ = 0.036 (ρ <0.05), so this means that there is a correlation between breakfast habits and the incidence of anemia. Based on the RR value is 1.24, so the risk of students not having breakfast for anemia is 1.2 times higher than students who have breakfast habits.